Pengembangan E-Modul Berbasis Kearifan Lokal Daerah Grobogan untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Novita Kumalasari; Irfai Fathurohman; Fina Fakhriyah (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the effectiveness of e-module teaching materials based on the local wisdom of the Grobogan area on the learning outcomes of elementary school students. This research method used research and development from Borg and Gall and used the One Group Pretest-Posttest Design. The data collection used was pretest and posttest description test questions supplemented by an assessment rubric given to students. The data analysis technique of this study used the Independent Sample T-Test and the N-Gain Score test. The results of this study indicated that the effectiveness of the e-module teaching materials that have been tested gets t-test results with a sig (2-tailed) of 0.000 ˂ 0.05, which indicates a significant difference between the results of the students' pretest and posttest. While the average N-Gain score of students in one class, when viewed from the N-Gain percent by using the category of interpretation of the effectiveness of the N-Gain score, is declared